Base mathematical models of process of transmission of mechanical energy during drilling of exploraty and geotechnological wells - V. V. Kulikov; M. S. Frolova (Известия высших учебных заведений: Геология и разведка)
The most general mathematical models of transmission of mechanical energy from the drilling rig and boring pump in a mining hole are considered in the paper. Additive, proportional and generalized models of process of transmission of energy are grounded and offered. The base additive mathematical model of transmission of mechanical energy is underlain in the basis of the traditional method of calculation of energy consumption at well-drilling and calculation of hydraulic resistances in a mining hole. Basic property of the additive model is absence of cross-coupling of different parts of transmission of energy. The base proportional mathematical model of transmission of mechanical energy is characterized by the followings properties: the values of the coefficient of efficiency of the parts of transmission of energy ratios stay unchanging; general coefficient of efficiency of all areas remains unchanging; at the different areas of transmission of energy the spent power changes in different number of times; the areas of transmission of energy mutually influence on each other; the maximum degree of influence is possessed by the last area, the least one is in the first area.